ADAPTASI KOMUNIKASI ISTRI DALAM ORGANISASI BHAYANGKARI DAN PERSIT KARTIKA CHANDRA KIRANA - Rosa Humaira, Almira; Rahardjo, Turnomo; Dwiningtyas Sulistyani, Hapsari (Interaksi Online, 2024)
The wives of TNI-Polri members are inseparable from their husband's institutions. For married TNI-Polri members, their wives play an important role in the smooth progression of their careers. Therefore, every wife who automatically joins the Bhayangkari and Persit organizations needs to adapt to the culture within these organizations. The research findings show that Bhayangkari members can learn the organizational culture earlier through the initial socialization they receive, while Persit members tend to learn over time through organizational activities. Spouses are the primary source of information for each informant about the organizational culture. Bhayangkari and Persit are collectivist organizations, although they share similarities in hierarchical structure with TNI-Polri institutions. Relationships among Bhayangkari members tend to be more complex, with more conflicts involving senior-junior power relations. Hierarchical communication is an essential aspect that wives need to understand to adapt effectively. Communication adaptation tends to be done through convergence by adopting the language style present in the organizational environment, adjusting gestures to match the interlocutor, and regulating the length of conversations in interactions.